Interpregnancy interval and adverse birth outcomes: a population-based cohort study of twins - Gursimran Dhamrait; Melissa O'Donnell; Hayley Christian; Catherine L. Taylor; Gavin Pereira (BMC, 2024)
Abstract Background To investigate associations between interpregnancy intervals (IPIs) and adverse birth outcomes in twin pregnancies. Methods This retrospective cohort study of 9,867 twin pregnancies in Western Australia from 1980-2015. Relative Risks (RRs) were estimated for the interval prior to the pregnancy (IPI) as the exposure and after the pregnancy as a negative control exposure for preterm birth (< 37 weeks), early preterm birth (< 34 weeks), small for gestational age (SGA: < 10th percentile of birth weight by sex and gestational age) and low birth weight (LBW: birthweight < 2,500 g). Results Relative to IPIs of 18-23 months, IPIs of < 6 months were associated with a higher risk of early preterm birth (aRR 1.41, 95% CI 1.08-1.83) and LBW for at least one twin (aRR 1.16, 95% CI 1.06-1.28). IPIs of 6-11 months were associated with a higher risk of SGA (aRR 1.24, 95% CI 1.01-1.54) and LBW for at least one twin (aRR 1.09, 95% CI 1.01-1.19). IPIs of 60-119 months and ≥ 120 months were associated with an increased risk of preterm birth (RR 1.12, 95% CI 1.03-1.22; and (aRR 1.25, 95% CI 1.10-1.41, respectively), and LBW for at least one twin (aRR 1.17, 95% CI 1.08-1.28; and aRR 1.20, 95% CI 1.05-1.36, respectively). IPIs of ≥ 120 months were also associated with an increased risk of early preterm birth (aRR 1.42, 95% CI 1.01-2.00). After negative control analysis, IPIs ≥ 120 months remained associated with early preterm birth and LBW. Conclusion Evidence for adverse associations with twin birth outcomes was strongest for long IPIs.